2020
DOI: 10.5334/aogh.2850
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns in Epidemiology of Malaria Between 2006 and 2018 in the South of Fars Province, Southern Iran: The Fall and Rise of Malaria

Abstract: Background: Malaria is one of the major human health problems that have become increasingly important in recent decades. Objective: The present study aimed to identify the epidemiological status of malaria in the years 2006–2018 in the southern region of Fars province in southern Iran. Methods: This is a cross-sectional descriptive-analytical study. The study population consisted of all persons with malaria referred to the Center for Disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Iran had previously reported indigenous malaria cases [ 2 , 7 ]. Consistent with recent data, previous studies had also reported a declining trend in the incidence of indigenous malaria cases in Iran [ 33 , 61 , 62 ]. However, imported malaria cases continue to occur.…”
Section: Epidemiology Of Malaria In Other Countries In the Middle supporting
confidence: 90%
See 2 more Smart Citations
“…Iran had previously reported indigenous malaria cases [ 2 , 7 ]. Consistent with recent data, previous studies had also reported a declining trend in the incidence of indigenous malaria cases in Iran [ 33 , 61 , 62 ]. However, imported malaria cases continue to occur.…”
Section: Epidemiology Of Malaria In Other Countries In the Middle supporting
confidence: 90%
“…Plasmodium vivax was the dominant species, identified in 478 (88%) individuals while 63 (12%) patients were infected with P. falciparum [ 61 ]. Delam et al [ 62 ] described the epidemiological status of malaria in the southern region of Fars Province in southern Iran during 2006–2018. The authors found a total of 190 cases of malaria with >95% infections affecting Afghans and most of them were workers.…”
Section: Epidemiology Of Malaria In Other Countries In the Middle mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of climate, Larestan, Evaz and Khonj are considered as arid regions, and the average annual rainfall in these regions from 2003 to 2010 was about 151.8 mm [21]. Larestan city is the largest city in Fars province in terms of area, which is located in the south of this province (Figure 1) [22].…”
Section: Study Areamentioning
confidence: 99%
“…The remaining 4 cases had mixed infection of P. falciparum and P. vivax . The study carried out in the southern region of Fars province in Iran also detected nearly all malaria cases among Afghan nationals, mostly including migrant workers, during 2006–2018 [ 86 ].…”
Section: Malaria Status Among Countries Contributing Most Of the Imported Malaria Cases In Gcc Countriesmentioning
confidence: 99%